ANALYZE THE PERFORMANCE OF HORNS WITH COMPLEX WORKING SURFACES USED IN ULTRASONIC WELDING OF CAR TURN SIGNALS - Nhu Khoa, Ngo; Anh-Tuan, Dang; Nguyen, Dinh-Ngoc (Journal of Applied Engineering Science, 2024)
Ultrasonic plastic welding technology has been widely applied in practice. Welding horn design is one of the important tasks. Many studies have presented this problem. However, most of these studies are only interested in face profiles that are flat or have symmetrical profiles. Meanwhile, ultrasonic welding horns with complex working surfaces receive little attention. This research presented the design of an ultrasonic horn with a complex working surface. Moreover, the influence of the slot width in the horn, an important design parameter, on the performance of the designed horn was considered. The finite element method was used for modal and harmonic analysis. The performance of the design was assessed through criteria that are the uniformity of amplitude, the distribution of the greatest stress at points on the working surface, and closed to the target frequency. A new parameter, namely Displacement unevenness (a), was proposed to evaluate the unevenness amplitude in the working surface of the horn. Effects of three alternative slot structures width corresponding values of 12 mm, 17 mm and 20 mm, denoted by B12, B17, and B20 respectively were carried out. The results showed that the B12 and B17 designs have natural frequencies close to the target frequency of the welding machine, while the natural frequency of the B20 design is far from the target one. The B12 and B17 designs also produce an unevenness amplitude smaller than those of the B20 design. The model showing the relationship between design parameters and the required criteria must be further developed. Additionally, this result can be said for the design guidelines not fully available in the literature.